2021
DOI: 10.1002/cjce.24064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coal particle size on gasification performance of two‐stage entrained‐flow coal gasifier

Abstract: To clarify the effect of coal particle sizes on gasification performance of an advanced two-stage entrained-flow coal gasifier for IGCC (integrated gasification combined cycle) application, a comprehensive three-dimensional numerical model is established by incorporating the shrinking core model combined with the Langmuir-Hinshelwood kinetic rate expression, which considers the inhibitory effect of CO on char-CO 2 reaction. The flow, temperature, and species distributions were obtained, and the results are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To verify the accuracy of the numerical models, the simulation results including the gas composition and carbon conversion efficiency are compared with the industrial data. 19 Fan et al’s simulation results, 39 which used a simplified PDF model to describe the interaction of turbulence and gas-phase chemical reactions, are also compared. As presented in Table 6 , the predictions presented in this work show favorable agreement with the industrial data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the accuracy of the numerical models, the simulation results including the gas composition and carbon conversion efficiency are compared with the industrial data. 19 Fan et al’s simulation results, 39 which used a simplified PDF model to describe the interaction of turbulence and gas-phase chemical reactions, are also compared. As presented in Table 6 , the predictions presented in this work show favorable agreement with the industrial data.…”
Section: Resultsmentioning
confidence: 99%
“…The second stage of the gasifier was set to “reflect”. The thermal conditions of the wall were set as “convection” with an equivalent convective heat transfer coefficient of 169 W/m 2 K in the first stage and 121 W/m 2 K in the second stage, assuming a free stream temperature of 473 K. 39 The internal emissivity of the refractory brick was set to be 0.6. The discrete ordinate (DO) radiation model coupled with the weighted-sum-of-gray-gases model (WSGGM) was adopted to calculate radiative heat transfer.…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…Hence, higher conversion is expected for smaller particles for a certain coal feed rate. [ 5 ] Fan et al [ 19 ] studied the effect of coal size on gasification performance and found that an eight recirculation zones observed in the two‐stage entrained flow gasifier increase the residence time of particles. Jayaraman et al [ 20 ] studied the effect of heating rate on the kinetics of steam and CO 2 gasification in high ash coal and found that with an increase in the heating rate, the reactivity of char gasification increases.…”
Section: Introductionmentioning
confidence: 99%